RANCANG BANGUN SISTEM INFORMASI PONDOK PESANTREN AL-GHOZALI BERBASIS ANDROID - Moch.farhan Ahadi; Weni Gurita Aedi (CV. Multi Kreasi Media, 2022)
The theme of the research carried out is an effort to design information system buildings in Islamic boarding schools from manual and paper-based methods using technology devices and digital-based information systems with Android and Desktop applications. The object of the research was carried out in an educational institution, namely the modern Al-Ghozali Islamic boarding school which is located in the Gunung Sindur District, Bogor Regency. The data collection technique used in this study was by distributing questionnaires, observing and interviewing students, parents of students and managers of Islamic boarding schools to identify research problems, then based on these problems, data processing, data analysis, and conclusions were drawn. From the results of data analysis, an application design with the waterfall method was made in building software whose processing uses the PHP programming language, Java and database supported by software such as Android Studio, Visual Studio Code, and Mysql. The results of this application design are expected to provide solutions and problem solving for Islamic boarding schools in overcoming various problems that have been using paper and manual media and then switching to digital systems. The scope of the information system design includes the acceptance of new students including registration fees, selection schedules, selection fees, payment methods, announcement of selection results and other information related to Islamic boarding school activities. With the hope that prospective students, students and parents can easily, practically and completely access the variety of information offered by the Islamic boarding school.